Factors Associated with Medication Noncompliance in Dogs in New Zealand. - Odom TF; Riley CB; Benschop J; Hill KE (MDPI (Basel, Switzerland), 2024)
Client compliance with prescribed medication instructions to treat their pets is a concern. This study describes factors associated with the noncompliance of dog owners with veterinary recommendations for medication, as well as client-reported barriers and aids to administering medications. A cross-sectional survey of dog owners' compliance with veterinary medication recommendations was performed from 9 January 2019 to 18 July 2020. A convenience sample of owners who prescribed medication for their dogs during or following elective veterinary examination was surveyed regarding medication administration experience and compliance. Owners were followed up to determine if the course of medication had been completed. Compliance data were analyzed descriptively. Logistic regression was performed with compliance as the outcome. Medication noncompliance was recorded for 47% (71/151) of owners. Increasing dog age was associated with better owner compliance (p < 0.05). Pet owners who used "nothing" as an aid to medicating were less likely to be noncompliant (p < 0.05). Forty-seven percent (71/151) of owners reported that "nobody" showed them how to administer the medication. One-third of dog owners (47/151) reported challenges in medicating their pets. The most common reason cited by clients reporting challenges was a resistant pet. Demonstration of medication administration techniques and discussion about available aids to medicating a pet may improve client compliance.
Keywords: adherence; compliance; dog; medication; persistence; pet owner; survey